2018
DOI: 10.1002/pds.4563
|View full text |Cite
|
Sign up to set email alerts
|

Early impact of the ICD‐10‐CM transition on selected health outcomes in 13 electronic health care databases in the United States

Abstract: When using data from both the ICD-9-CM and ICD-10-CM eras, or when using results from ICD-10-CM data to compare to results from ICD-9-CM data, researchers should test multiple ICD-10-CM outcome definitions as part of sensitivity analysis. Ongoing assessment of the impact of ICD-10-CM transition on identification of health outcomes in US electronic health care databases should occur as more data accrue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 27 publications
1
45
0
Order By: Relevance
“…The US Centers for Medicare and Medicaid Services (CMS) formally set October 1, 2015, as the compliance date for conversion from the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) to ICD‐10 diagnostic (ICD‐10‐CM) and procedure (ICD‐10‐PCS) codes . We previously performed a series of descriptive analyses to assess the impact of the coding transition on changes in the incidence and prevalence of select health outcomes and found that outcomes should be assessed on a case‐by‐case basis . Replicating well‐established exposure‐outcome associations in the ICD‐10‐CM era or the period spanning across both ICD‐9‐CM and ICD‐10‐CM eras may also help explore the implications of the transition on drug safety analyses and discover best practices toward minimizing unwanted consequences.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…The US Centers for Medicare and Medicaid Services (CMS) formally set October 1, 2015, as the compliance date for conversion from the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM) to ICD‐10 diagnostic (ICD‐10‐CM) and procedure (ICD‐10‐PCS) codes . We previously performed a series of descriptive analyses to assess the impact of the coding transition on changes in the incidence and prevalence of select health outcomes and found that outcomes should be assessed on a case‐by‐case basis . Replicating well‐established exposure‐outcome associations in the ICD‐10‐CM era or the period spanning across both ICD‐9‐CM and ICD‐10‐CM eras may also help explore the implications of the transition on drug safety analyses and discover best practices toward minimizing unwanted consequences.…”
Section: Introductionsupporting
confidence: 73%
“…We defined an angioedema event using ICD‐9‐CM (995.1, angioneurotic edema not elsewhere classified) and ICD‐10‐CM codes (see below) that appeared on an inpatient, outpatient, or emergency department claim. We used simple‐forward mapping (SFM), simple‐backward mapping (SBM), and forward‐backward mapping (FBM) referencing the 2017 General Equivalence Mappings (GEMs) from the Centers for Medicare and Medicaid Services to define angioedema in the ICD‐10‐CM era based on the ICD‐9‐CM definition . Briefly, in SFM, translation of ICD‐9‐CM to ICD‐10‐CM codes is conducted by referencing the ICD‐9‐CM to ICD‐10‐CM GEMs conversion file, which contains all ICD‐9‐CM codes (approximately 17 000) mapped to ICD‐10‐CM codes .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of ICD‐10‐CM took effect in October 2015 in the United States, thus accuracy of ICD‐10‐CM codes may evolve. Establishing how codes are presently being used is necessary to allow for monitoring of trends . There were 226 cases (15.0%) among the initial 1500 patients eligible for the study that were not available for review; however, because cases were randomly assigned to reviewers, we would not expect this to bias the study findings.…”
Section: Discussionmentioning
confidence: 99%
“…A number of US studies have evaluated the financial impact or differences in incidence or prevalence of adverse health outcomes between the period before and after the transition to ICD-10-CM (Hellman, Lim, Leung, Blount, & Yiu, 2018;Inscore, Gonzales, Rennix, & Jones, 2018;Panozzo et al, 2018). However, the effect of this transition on birth defects prevalence and trends has not been explored.…”
Section: Introductionmentioning
confidence: 99%